"Análisis de las condiciones de vida de las microempresas formales del sector comercial en la parroquia de Cumbayá". - Maigua Cachimuel, José Marcelo (2015)
This degree work aims to establish the characteristics of real life conditions where formal microenterprises in the commercial section operate in Cumbayá parish; Taking into account until the present date. It does not find detailed data in commercial entrepreneurs of this segment. So, the personal aplication survey was used as a measuring tool. In the results characteristics affecting microenterprises as the following are observed. The mayority of locals of this sector are leased and paid from $100 to $1,700. More than half do not have credits with the financial institutions. The months of selling, a lot, are May and December. For most microenterprises monthly income is sufficient to support families and these range from $150 to $10,000 or more. In the family of microenterprises a person as minimum and maximum 5 perceive and additional income. Best selling products in this sector are the necessities and luxuries. Initial capital is not known among microenterprises in the middle of all locals. Most of microenterprise shaves from 1 to 5 employees and salary costs are within $349 and $ 1,750. Level of instruction of most owners is baccalaureate or higher students. The Cumbayá parish is an expanding sector entrepreneurs engaged in trade. They should improve establishing a diagnosis on the situation of their companies to take decisions that lead them to an improvement and to achieve the "Sumac Kawsay", life quality, for entrepreneurs and their environment. The urban growth of the capital city extends into their parishes which present a unique expansion due to existence of its own characteristics, such as the Cumbayá parish.